Once upon a dream eaudiobook - Braswell, Liz (Twisted Tales, 2016)
What if the sleeping beauty never woke up? Once Upon a Dream marks the second book in a new YA line that reimagines classic Disney stories in surprising new ways. It should be simple—a dragon defeated, a slumbering princess in a castle, a prince poised to wake her. But when the prince falls asleep as his lips touch the fair maiden's, it is clear that this fairy tale is far from over. With a desperate fairy's last curse controlling her mind, Princess Aurora must escape from a different castle of thorns and navigate a dangerously magical landscape—created from her very own dreams. Aurora isn't alone—a charming prince is eager to join her quest, and old friends offer their help. But as Maleficent's agents follow her every move, Aurora struggles to discover who her true allies are and, moreover, who she truly is. Time is running out. Will the sleeping beauty be able to wake herself up?